Quadriceps-splitting midline approach in the treatment of distal femur infected nonunion with stiff knee and severely scarred soft tissues - Bliss, Jeremy; Inja, Dan Barnabas; Nithyananth, Manasseh; Cherian, Vinoo Mathew (International Journal of Research in Orthopaedics, 2020)
Background: Treatment of infected distal femur non-union with a stiff knee and severely scarred soft tissues is a challenging problem. We describe a method of addressing the non-union using quadriceps splitting approach to the distal femur. Methods: We retrospectively reviewed 5 patients with distal femur infected nonunion and knee stiffness, who, after infection control, required distal femur bone grafting. All patients had autogenous iliac crest bone grafting of the distal femur using the quadriceps splitting approach. The parameters assessed were the time to surgical wound healing, wound infection, time to bony union, and if any additional procedures were needed. Results: 5 patients were referred with distal femur infected non-union in addition to knee stiffness, with or without an implant in situ. All patients underwent debridement, implant exit, and external fixation of the femur spanning the knee as the primary surgery here, followed later on by iliac crest bone grafting of the distal femur using the above approach. All patients united well within 12 to 16 weeks, without the need for additional procedures. Conclusions: In the presence of pre-existing knee stiffness with severely scarred and contracted soft tissues the quadriceps-splitting approach is a useful method to address bony problems in the distal femur, without the need for a separate procedure for soft tissue or flap cover.